2000
DOI: 10.1084/jem.193.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Chemokines of Circulating Dendritic Cell Precursors, and the Formation of Portal Tract–Associated Lymphoid Tissue, in a Granulomatous Liver Disease

Abstract: We have studied the recruitment and roles of distinct dendritic cell (DC) precursors from the circulation into Propionibacterium acnes–induced granulomas in mouse liver. During infection, F4/80−B220−CD11c+ DC precursors appeared in the circulation, migrated into the perisinusoidal space, and matured within newly formed granulomas. Recruited DCs later migrated to the portal area to interact with T cells in what we term “portal tract–associated lymphoid tissue” (PALT). Macrophage inflammatory protein 1α attracte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
214
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 190 publications
(229 citation statements)
references
References 48 publications
13
214
2
Order By: Relevance
“…Two major DC subsets have been identified on the basis of CD8␣ expression, namely CD8␣ ϩ and CD8␣ Ϫ DCs, and much has been studied on the differentiation pathways for these DC subsets (2,6). It has been reported that CD8␣ ϩ DCs, termed ''lymphoid DCs,'' are derived from CD8␣ ϩ CD11c Ϫ precursor cells in the spleen (7), whereas most of CD8␣ Ϫ DCs, termed ''myeloid DCs'', are derived from MHC class II Ϫ CD11c ϩ peripheral blood DC precursors (8,9). Some studies suggest that CD8␣ ϩ DCs produce IL-12 and prime Th1 responses whereas CD8␣ Ϫ DCs prime Th2 responses (10).…”
mentioning
confidence: 99%
“…Two major DC subsets have been identified on the basis of CD8␣ expression, namely CD8␣ ϩ and CD8␣ Ϫ DCs, and much has been studied on the differentiation pathways for these DC subsets (2,6). It has been reported that CD8␣ ϩ DCs, termed ''lymphoid DCs,'' are derived from CD8␣ ϩ CD11c Ϫ precursor cells in the spleen (7), whereas most of CD8␣ Ϫ DCs, termed ''myeloid DCs'', are derived from MHC class II Ϫ CD11c ϩ peripheral blood DC precursors (8,9). Some studies suggest that CD8␣ ϩ DCs produce IL-12 and prime Th1 responses whereas CD8␣ Ϫ DCs prime Th2 responses (10).…”
mentioning
confidence: 99%
“…These inflammatory cells include not only antigen-specific T cells but also nonspecifically activated immune cells. Chemokines and chemokine receptors are known to play an important role in the accumulation of inflammatory cells in liver diseases (Grant et al, 2002;Kusano et al, 2000;Marra et al, 1998;Narumi et al, 1997;Nishioji et al, 2001;Shields et al, 1999;Shimizu et al, 2001;Tamaru et al, 2000;Tsuneyama et al, 2001;Yoneyama et al, 2001). Chemokines such as IFNinducible protein-10, monokine-induced IFN-␥, and macrophage inflammatory protein-1 (MIP-1) have been suggested to play a role in the accumulation of T cells in the human liver of viral hepatitis and autoimmune hepatitis (AIH).…”
mentioning
confidence: 99%
“…In viral hepatitis and autoimmune liver diseases, many inflammatory cells accumulate in the portal tract, which is regarded as the secondary lymphoid tissue (Grant et al, 2002;Yoneyama et al, 2001). These inflammatory cells include not only antigen-specific T cells but also nonspecifically activated immune cells.…”
mentioning
confidence: 99%
“…Yoneyama et al recently reported that P. acnes-induced activation and recruitment of DCs in the liver is an initial event and is a prerequisite for liver injury in this model. 6,7 Furthermore, activated DCs have been shown to move to the hepatic regional lymph nodes (hepatic LNs) and activate P. acnes-specific CD4 ϩ T cells. Those are then recruited to the liver; the result of which is an accumulation of more T cells, macrophages, and DCs producing various chemokines.…”
mentioning
confidence: 99%